Transvaginal repair of total vaginal vault prolapse with polypropylene mesh. Presentation of five cases - Molina Loza, Ernesto (2015)
Objectives: To determine the feasibility, safety and efficacy of transvaginal surgical repair of total vaginal vault prolapse using polypropylene handicraft mesh. Design: Descriptive, retrospective, transversal study. Setting: Hospital IV Huancayo, EsSalud, Peru. Patients: Patients with diagnosis of total vaginal vault prolapse and previous hysterectomy. Interventions: Between October 2009 and June 2010 medical records of five patients with diagnosis of total vaginal vault prolapse and history of hysterectomy were reviewed. All patients underwent transvaginal surgical correction of total vaginal vault prolapse using polypropylene handicraft prosthetic mesh. Main outcome measures: Successful repair of vaginal vault prolapse. Results: Successful repair was obtained in all cases with no complications during surgery or in the postoperative period. Operative time ranged between 75 and 90 minutes. There are no recurrences to date. All patients expressed their total satisfaction with the results achieved. Conclusions: Surgical repair of total vaginal vault prolapse with use of handicraft prosthetic material (polypropylene mesh) is feasible, safe and effective and with less cost. Long-term results will allow us to know excellence of this technique.